Self-Reflection and Peer Feedback Practices: An Exploratory Study on the Sekolah Penggerak Program - Fatawi, Izzul; Abidin, Achmad Anwar (Journal of Education and Religious Studies, 2024)
This study aims to explore the implementation of self-reflection and peer feedback in supporting the professional development of educators within the Program Sekolah Penggerak (PSP). Using a qualitative descriptive-exploratory approach, data were collected through Focus Group Discussions (FGD) involving educators from the first cohort of PSP schools in East Lombok Regency. The findings indicate that self-reflection is conducted as an instrument of pedagogical evaluation, adaptation of teaching strategies, cross-level collaboration, and transformation of attitudes and teaching approaches. Peer feedback provides a platform for educators to share experiences, receive constructive input, and identify more effective teaching methods. These findings highlight the effectiveness of these practices in improving classroom learning quality and underscore their potential to foster an inclusive, collaborative, and innovative learning culture. Despite challenges such as time constraints, technological gaps, and a reflective culture that has yet to develop fully, the study's conclusions provide valuable insights for educators, policymakers, and researchers interested in professional development in education. Recommendations are directed towards strengthening technical support, enhancing educators' capacity, and improving coordination to ensure the sustainability of reflective programs in schools throughout Indonesia